Extension Strategies Based on Socio-Cultural Capital in Marine and Fisheries Extension - Muhammad Yusuf (PT FORMOSA CENDEKIA GLOBAL, 2023)
The existence of fishery instructors is very important in supporting development in the marine and fisheries sector. Including the implementation of an extension strategy based on community social capital where it is important for fisheries extension officers to pay attention to the levels of the main actors and business actors which include individual character, but also group character, signs of networks between groups, and the nature of networks with people in the community. outside the community